Gestational Weight Gain Trend and Population Attributable Risks of Adverse Fetal Growth Outcomes in Ohio. Issue 4 (5th June 2015) - Chen, Aimin; Xu, Fan; Xie, Changchun; Wu, Tianying; Vuong, Ann M.; Miao, Maohua; Yuan, Wei; DeFranco, Emily A.
Abstract Background The trend of gestational weight gain (GWG) in relation to the Institute of Medicine (IOM) guidelines and the population attributable risks (PARs) of GWG on fetal growth outcomes remain unclear. Methods We analysed Ohio birth certificates from 2006 to 2012 to examine GWG trend by prepregnancy body mass index, to calculate the risk of small‐ and large‐for‐gestational age (SGA and LGA), and macrosomia (birthweight >4000 g or >4500 g) infants, and to estimate the PARs of GWG below or above the guidelines. Results Of 869 531 women who delivered singleton live births at 22–44 weeks of gestation, 4.5% were underweight, 48.9% were normal weight, 23.9% were overweight, and 22.7% were obese before pregnancy. About 36.5% of underweight, 52.6% of normal weight, 72.5% of overweight, and 62.4% of obese women gained weight above the guidelines, with only slight changes from 2006 to 2012. Also, 34.9% of underweight, 20.1% of normal weight, 16.3% of overweight, and 27.0% of obese women gained weight below the guidelines. The PAR of GWG below or above the guidelines was −13% for SGA, 32.6% for LGA, 28.1% for macrosomia >4000 g, and 48.3% for macrosomia >4500 g, mostly driven by currently GWG above the guidelines in normal weight, overweight, and obese women. Conclusions A high percentage of pregnant women gained weight outside of the current IOM GWG guidelines; however, changes from 2006 to 2012 were small. GWG above the IOM guidelines significantly contributed to a large proportion of LGA and macrosomic infants in the general population.